EVALUATING REGIONAL TRANSPORT ACCESSIBILITY - Яновський, П.О.; Матійчик, О.М. (Science-based technologies, 2013)
The approaches to evaluate the accessibility of passenger transport on regional level are considered. Components and measures for evaluation of passenger transport accessibility are grouped. The notion of integral transport accessibility for evaluating the level of regional transport infrastructure development is formalized. The significance of the level of transport accessibility for transportation demand satisfaction and its influence on mobility of population. The relationship between the notion of integral transport accessibility and occurrence of the notions of transport discrimination and transport inaccessibility is stated. The factors of evaluating regional transport accessibility are analyzed and the possible variants of strategies for its promotion are suggested